2022
DOI: 10.3390/cancers14030828
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Hepatocellular Carcinoma Development and Predictive Ability of Non-Invasive Scoring Systems in Patients with HCV-Related Cirrhosis Treated with Direct-Acting Antivirals

Abstract: Patients with hepatitis C virus (HCV)-related cirrhosis treated with direct-acting antivirals (DAA) are still at risk of developing hepatocellular carcinoma (HCC). We investigated the accuracy of non-invasive scoring systems (NSS) for the prediction of de novo HCC development in patients treated with DAA on long-term follow-up (FU). We analyzed data from 575 consecutive patients with cirrhosis and no history of HCC who achieved a sustained virologic response (SVR) to DAA therapy. NSS (i.e., Forns index, APRI, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 33 publications
0
18
1
Order By: Relevance
“…The cumulative incidence of HCC after SVR observed in this study was not significantly different from that reported in other studies (22,29,30). HCC occurred sporadically for at least 5 years after SVR with IFN-free treatments in this study involving a population with a mix of patients at high and low risk for HCC.…”
Section: Ii) Cumulative Incidence Of Hcc After Svrcontrasting
confidence: 64%
“…The cumulative incidence of HCC after SVR observed in this study was not significantly different from that reported in other studies (22,29,30). HCC occurred sporadically for at least 5 years after SVR with IFN-free treatments in this study involving a population with a mix of patients at high and low risk for HCC.…”
Section: Ii) Cumulative Incidence Of Hcc After Svrcontrasting
confidence: 64%
“…The ALBI score is strongly associated with the degree of hepatic fibrosis, as assessed by the FIB-4 (fibrosis-4) index 81 , 82 or aspartate aminotransferase-to-platelet ratio index (APRI). 83 This observation presumably explains several reports that the ALBI score is an important risk factor for HCC development, 67 , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] particularly after sustained virologic response. [86] , [87] , [88] The best documented risk score for HCC in patients with chronic liver disease is the aMAP score 89 , 90 which combines ALBI with age, male sex and platelet count and may form the basis of a realistic risk stratification strategy.…”
Section: Beyond Hcc: Application Of the Albi Score/grade In General H...mentioning
confidence: 68%
“…The ALBI score is strongly associated with the degree of hepatic fibrosis as assessed by the FIB-4 index [81,82] or APRI [83]. This observation presumably explains several reports that the ALBI score is an important risk factor for HCC development [67,[74][75][76][77][78][79][80][81][82][83][84][85][86][87][88] particularly after sustained virologic response [86][87][88].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 78%
See 1 more Smart Citation
“…Fibroscan values were measured by ultrasound elastography in 55 patients (44 CLD and 11 non-CLD patients) to assess liver stiffness. The albumin-bilirubin (ALBI) score was calculated as log 10 total bilirubin ( μ mol/L) × 0.66 + albumin (g/L) × −0.085 [ 17 ]. This study was approved by the Research Ethics Committee, Zhongshan Hospital Fudan University.…”
Section: Methodsmentioning
confidence: 99%